Changes in the ocular surface condition during the transition to preservative-free hypotensive combination therapy in the long-term observation of patients with advanced stages of glaucoma - Dmitry A. Dorofeev; Aleksandr A. Vitkov; Elena V. Kirilik; Ksenia O. Lukyanova; Olga G. Pozdeeva (Russian Open Medical Journal)
Overview — Elevated intraocular pressure (IOP) is the main risk factor for the development and progression of primary open-angle glaucoma (POAG). Topical drugs, along with laser and surgical treatment options, are among the methods of IOP reduction. In most cases, topical hypotensive therapy is considered the first stage of glaucoma treatment. The transition to other treatment methods often occurs due to the ineffectiveness of long-term combination therapy. Most of the drugs used contain a preservative, which can negatively affect the condition of the ocular surface. The use of preservative-free fixed combinations (FC) can improve it with a similar hypotensive effect. Objective — To study the condition of the ocular surface when replacing the preserved FC of brinzolamide 1%/timolol 0.5% with a preservative-free FC of tafluprost 0.0015%/timolol 0.5%. Material and Methods — Group 1 (observation group) included patients with POAG in 20 (20.6%) eyes. Group 2 (control) included individuals without glaucoma who did not receive topical therapy in 77 (71%) eyes. The final study protocol included observational data at the time of inclusion in the study, as well as 1 month and 1 year after replacing the preserved FC of brinzolamide 1%/timolol 0.5% to the preservative-free FC of tafluprost 0.0015%/timolol 0.5%. All patients underwent a standard ophthalmological examination and assessment of structural and functional parameters, as well as examination of their ocular surface condition via the Norn test, Schirmer test, lissamine green vital staining, the Ocular Surface Disease Index (OSDI) questionnaire, and meniscometry 1 month and 1 year after the onset of the study. Results — Results: No statistically significant changes in IOP were observed after switching from the preserved FC of brinzolamide 1%/timolol 0.5% to the preservative-free FC of tafluprost 0.0015%/timolol 0.5% (from 13.4±2.7 to 13.4±3.2 mmHg after 1 month and to 15.3±4.4 mmHg after 1 year). At all checkpoints, the condition of the ocular surface was similar between the groups (p>0.05) for all parameters, except for the OSDI questionnaire. After 1 month and 1 year of observation, no significant changes in the ocular surface were found in the groups using preservative-free Tapticom ® (Santen, Japan), except for the OSDI questionnaire after 1 year. The ratio of the tear meniscus depth and height based on OCT meniscometry data statistically significantly differed between the groups. Conclusion — Long-term use of preservative-free Tapticom ® allowed effectively reducing the IOP to target values. This helped stabilizing structural and functional parameters without causing additional changes in the condition of the ocular surface. The transition from long-term treatment with preserved medications to preservative-free drug forms does not always lead to an improvement in the condition of the eyes. This may be due to a chronic process provoked by the preservative. Prescribing preservative-free therapy at the onset of treatment allows reducing the risk of developing dry eye syndrome and diminishing the subjective sensations in patients during long-term hypotensive therapy.